2019
DOI: 10.1111/eva.12751
|View full text |Cite
|
Sign up to set email alerts
|

Fitter frogs from polluted ponds: The complex impacts of human‐altered environments

Abstract: Human‐modified habitats rarely yield outcomes that are aligned with conservation ideals. Landscapes that are subdivided by roads are no exception, precipitating negative impacts on populations due to fragmentation, pollution, and road kill. Although many populations in human‐modified habitats show evidence for local adaptation, rarely does environmental change yield outright benefits for populations of conservation interest. Contrary to expectations, we report surprising benefits experienced by amphibian popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 60 publications
3
22
0
Order By: Relevance
“…Interestingly, within individual differences in all of the color metrics between the first and second year occurred in the same direction as the differences in color metrics between males and females. Wood frog females generally take one year longer to reach sexual maturity than males (Berven 1982, Sagor et al 1998, and in a previous study, we found sex differences in age structure of reproductive individuals in our breeding ponds (Brady et al 2019). This suggests that the commonly reported sexual dichromatism in adult wood frogs could be explained, at least in parts, by demographic factors (i.e.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, within individual differences in all of the color metrics between the first and second year occurred in the same direction as the differences in color metrics between males and females. Wood frog females generally take one year longer to reach sexual maturity than males (Berven 1982, Sagor et al 1998, and in a previous study, we found sex differences in age structure of reproductive individuals in our breeding ponds (Brady et al 2019). This suggests that the commonly reported sexual dichromatism in adult wood frogs could be explained, at least in parts, by demographic factors (i.e.…”
Section: Discussionsupporting
confidence: 74%
“…Previous research on the effects of urbanization on wood frogs and other vernal pool amphibians provides some potential insights into the specific urban-related selection factors that may be causing the observed patterns. Roadside populations of wood frogs have been observed to have larger body sizes, higher fecundity, and better jumping performance than their nearby woodland counterparts (Brady et al In press). These indicators of greater fitness in roadside populations is juxtaposed by other observations of reduced growth rates for larval wood frogs from these environments (Hall et al 2017), suggesting road-associated effects may be variable across wood frog populations or life history stages.…”
Section: Discussionmentioning
confidence: 99%
“…Life history and behavioral characteristics such as short generation times (2–3 years; Berven 1990; Sagor et al 1998), small home ranges (Berven and Grudzien 1990; Groff et al 2017), and high rates of philopatry (Berven and Grudzien 1990) make wood frogs excellent candidate species for detecting evolutionary change over short time scales. Moreover, previous research suggests urban-associated landscape features such as roadways (Hall et al 2017; Brady et al In press) and open tree canopies (Skelly et al 2014) can influence wood frog fitness-related characteristics such as growth and fecundity rates, potentially as a result of, or a precursor to selection. In light of previous research on the evolutionary consequences of urbanization in other species, we tested 2 hypotheses: 1) genome-wide genetic diversity would be less in urban relative to rural populations and 2) signals of selection associated with urbanization would be detectable.…”
mentioning
confidence: 99%
“…Individuals used in this analysis were collected during the inbound breeding migration (prior to arriving at ponds) using drift fences with pitfall traps. Edema was estimated from photos as described above and age was estimated using skeletochronology of toe clips (methods described in Brady et al 2019). We used a linear model with either prevalence or severity as the response variable, and the interaction between age and population type for fixed effects.…”
Section: Edema Severity/prevalence and Environmental Variationmentioning
confidence: 99%
“…Frogs were placed on one end of a 0.91 X 5 m piece of brown paper and at least 5 consecutive jumps were recorded, or frogs were placed between two plastic walls (height: 34 cm; length: 3.4 m) separated by approximately 30 cm, such that frogs could only jump forward. Frogs were motivated to jump as needed by tapping their urostyle with a finger (Brady et al 2019). Marks were placed where frogs landed and the maximum distance between marks was recorded.…”
Section: Jumping Performancementioning
confidence: 99%